Analisis Literasi Halal Dan Preferensi Produk Yang Diboikot Pada Mahasiswa Universitas KH. A. Wahab Hasbullah - Amin Awal Amarudin; Novi Ria Ananta; Nurun Nisaul Khusna; Regita Juninda Berliani; Sri Oktavianah (Universitas Maritim AMNI Semarang, 2024)
College students, as a dynamic group developing their identity, are often the first to adopt new habits and styles. Therefore, it is important to know how students assess halal products and to what extent students avoid banned products. This research aims to determine students' knowledge about halal literacy and preferences for boycotted products. The results of the research show that the majority of KH University students. A. Wahab Hasbullah understands halal literacy, students look at halal products before consuming them and the majority of students are in the category of rarely consuming products that are considered boycotted. This research uses qualitative and quantitative methods.